Mortality rates from asbestos-related diseases in Italy during the first year of the COVID-19 pandemic - Fazzo, Lucia; Grande, Enrico; Zona, Amerigo; Minelli, Giada; Crialesi, Roberta; Iavarone, Ivano; Grippo, Francesco (Frontiers in Public Health, 2024)
Background and aim. Patients with interstitial lung diseases, including asbestosis, showed high susceptibility to SARS-CoV-2 virus and high risk of severe COVID-19 symptoms. Italy, highly impacted by asbestos related diseases, in 2020 was among the European countries with the highest number of COVID-19 cases. The mortality related to malignant mesotheliomas and asbestosis in 2020 and its relationship with COVID-19 in Italy are described. Methods. From the National Registry of causes of death, all death certificates involving malignant mesotheliomas or asbestosis in 2010-2020 were retrieved. Annual mortality rates and Rate Ratios (RRs) of 2020 and 2010-2014 compared to 2015-2019 were computed. The association of malignant pleural mesothelioma (MPM) and asbestosis with COVID-19 in deceased ≥ 80 years old was evaluated through a logistic regression (Odds Ratios: ORs), using MPM and asbestosis deaths without COVID-19 rates as reference. The hospitalization for asbestosis in 2010-2020, based on National Hospital Discharge Database, was analysed. Results. In 2020, 746,343 people died; out of them, 1338 involving MPM and 286 asbestosis. Compared to the previous periods the mortality involving the two diseases decreased in overall population; an increasing trend was observed in ≥ 80 years age class: RRs in 2020 vs average 2015-2019 significantly higher than one (MPM: RR=1.10; asbestosis: RR=1.17). Comparing the deaths with/without COVID-19, among the subjects ≥ 80 years deceased with MPM and asbestosis highlights that deaths with COVID-19 have a lower probability of presenting MPM in both genders (males: OR=0.22; females: OR=0.44), while no departure was observed for asbestosis. A decrease of hospitalization in 2020 with respect to 2010-2019 in all age classes, both considering asbestosis as primary or secondary diagnosis, was observed. Conclusions. An increasing mortality involving asbestosis and, even if of slight entity, MPM, was observed in people over 80 years , during the first year of COVID-19 pandemic. No direct association with COVID-19 mortality was observed. The exceeding mortality, partially in agreement with the previous temporal trend, could be due to several factors, including the reduction of healthcare during the pandemic period. Protection acts addressed to patients with asbestos related diseases during the pandemic periods are recommended.